2018
DOI: 10.1186/s13104-018-3698-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of antenatal and postnatal care in contraceptive use during postpartum period in western Ethiopia: a cross sectional study

Abstract: ObjectiveLittle has been known about the magnitude and predictors of contraceptive use in extended postpartum period in Ethiopia. Thus, this study aims to assess the magnitude and determinants of contraception utilization in extended postpartum period. A community based cross-sectional survey was conducted in Gida Ayana district, Oromia regional state, Ethiopia in February 2015. Six hundred and three postpartum women were included using a multistage sampling technique. Descriptive statistics were used to summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
37
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 12 publications
14
37
3
2
Order By: Relevance
“…These studies showed a dose-response type of relationship between antenatal care and postpartum contraception adoption; that is the likelihood of using postpartum contraception increased when women had frequent antenatal contacts. Our result also demonstrated a significant association between postpartum contraceptive use and early postnatal care, which is in agreement with other studies [20,27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These studies showed a dose-response type of relationship between antenatal care and postpartum contraception adoption; that is the likelihood of using postpartum contraception increased when women had frequent antenatal contacts. Our result also demonstrated a significant association between postpartum contraceptive use and early postnatal care, which is in agreement with other studies [20,27].…”
Section: Discussionsupporting
confidence: 93%
“…The finding is comparable with the finding of the study done in Debre Tabor town, Northwest Ethiopia 63.0% (95% CI: 59%; 67.4%) [26]. This result was, however, higher than the 31.7% prevalence in Southern Ethiopia [20], 45.4% in western Ethiopia [27], and 29.3% in Northern Ethiopia [19], and lower when compared to the studies done in Hosana town (72.9%), Addis Ababa, Ethiopia (80.3%), and 86.3% of Kenya [28][29][30]. The low level of contraceptive use found in this study might reflect the over-reliance of lactating women on breastfeeding and menstruation status.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Mothers who received antenatal care were 1.74 folds more likely to utilize modern contraceptive than mothers who did not received such care. These higher odds of modern contraceptive utilization are supported by findings reported from Ethiopia [19] and Nigeria [18]. The plausible reason might be that during antenatal care follow ups the mothers obtain counseling on birth spacing and family planning.…”
Section: Discussionsupporting
confidence: 69%
“…High contraceptive utilization has been documented among literate [13,14], old age [14], rural residences [13], media familiar and richest women [15] who have had many (> 5) live children [16,17]. Health care utilizations during pregnancy and after delivery, antenatal and postnatal care [18,19] and child immunization [20] also increase the likelihood of modern contraceptive utilization.…”
Section: Introductionmentioning
confidence: 99%